2020
DOI: 10.1101/2020.10.04.325522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteolytic activation of SARS-CoV-2 spike at the S1/S2 boundary: potential role of proteases beyond furin

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses its spike (S) protein to mediate viral entry into host cells. Cleavage of the S protein at the S1/S2 and/or S2’ site is known to activate the S protein for viral entry, which can occur at either the cell plasma membrane or the endosomal membrane. Previous studies show that SARS-CoV-2 has a unique insert at the S1/S2 site that can be cleaved by furin, which expands viral tropism to lung cells. Here, we analyze the presence of a furin S1/S2 si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 47 publications
(72 reference statements)
0
28
0
1
Order By: Relevance
“…Previous work has shown that treatment of MERS-infected Calu-3 cells with E64d, a broad cysteine protease inhibitor, had diminished efficacy presumably as a result of low CTSL expression but heightened TMPRSS2 expression. This shift in expression profile resulted in the predominant processing of the MERS spike protein by TMPRSS2 (38). It was also suggested that cleavage of the SARS-CoV-2 spike protein by TMPRSS2 in cells with low CTSL levels (such as Calu-3) is essential for efficient viral entry, whereas in TMPRSS2 negative cells (Vero E6) viral infection can proceed with high efficiency using CTSL (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that treatment of MERS-infected Calu-3 cells with E64d, a broad cysteine protease inhibitor, had diminished efficacy presumably as a result of low CTSL expression but heightened TMPRSS2 expression. This shift in expression profile resulted in the predominant processing of the MERS spike protein by TMPRSS2 (38). It was also suggested that cleavage of the SARS-CoV-2 spike protein by TMPRSS2 in cells with low CTSL levels (such as Calu-3) is essential for efficient viral entry, whereas in TMPRSS2 negative cells (Vero E6) viral infection can proceed with high efficiency using CTSL (39).…”
Section: Discussionmentioning
confidence: 99%
“… 60 Tang and his coworkers in their preprint studies in 2020 identified the presence of additional amino acid residue, P-R-R-A in SARS-CoV-2 at S1/S2 site that was not notified in SARS-CoV. 61 R-R-A-R amino acid residue at the S1/S2 site of S protein may be sensitive to furin dependent cleavage. 62 The activity of furin resides on this poly basic motif to activate the degradation of S protein to generate S2 and S1 subunits.…”
Section: Proteins Involved In Viral Entry Mechanismmentioning
confidence: 99%
“…Furin proteolysis at the S1-S2 boundary (681–685) and in S2 (811–815) exposes the RBD to enable hACE2 binding, and the S2 domain to initiate membrane fusion 5 . Recent studies show that these cleavage sites are not necessarily specific for furin-mediated proteolysis and that S protein may be processed by multiple proteases to open the RBD into the active conformation 2 4 , 33 . Consistent with these observations, both the furin proteolysis consensus sites and the arginines that are critical for proteolysis are not conserved in the S protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue relates to the furin cleavage sites. As the viral S protein activation appears to require furin proteolysis 2 4 , protease-specific inhibitors are tested as a means to protect from infection 48 . However, our analysis suggests that this may not be an effective strategy, given the high variability of furin cleavage sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation